Floor heave mechanism in water-rich soft rock roadways and a DS-IBA control approach. Issue 1 (31st December 2022) - Zhai, Wenli; He, Fulian; Xu, Xuhui; Lv, Kai; Li, Liang; Song, Jiayu
Abstract: Severe floor heave in underground soft rock roadways heavily affects mine safety and production efficiency. In the present study, the context of the Shanghaimiao mining area is analyzed as the research object. In this regard, the floor heave mechanism and floor control in water-rich soft rock roadways are investigated through laboratory experiments, theoretical analysis, numerical simulation, and field tests. Moreover, a mechanical model of asymmetric floor heave is established. The obtained results reveal that: the main contributors to serious floor deformation in mining roadways are low rock stratum strength, hydrophysical behavior, and mining disturbance. It is found that the roadway floor stability is relevant to the stress concentration coefficient of the roadway side, the burial depth of the roadway, and the cohesion and internal friction angle of the floor rock. Meanwhile, the correlation between the upward resultant stress of the floor and the stress concentration coefficient of the roadway sides is established. Furthermore, the horizontal stress distribution of the roadway floor within 20 m of the advanced working face is simulated and analyzed. Based on the performed analyses and the obtained results, a novel double-seal deep and shallow inverted bottom arch (DS-IBA) floor support strategy is proposed. The proposed strategy is expected to provide a reference for dealing with similar water-rich soft rock roadways.